Optimal fuzzy control using hedge algebras of a damped elastic jointed inverted pendulum - Le, Bui Hai; Trung, Tran Duc; Lan, Vu Nhu (Vietnam Journal of Mechanics, 2010)
In this paper, three controllers including OFCHA (optimal fuzzy control using hedge algebras-HAs), FCHA (fuzzy control using HAs) and CFC (conventional fuzzy control) are designed. Our attention is paid to the stability in the vertical position of a damped-elastic-jointed inverted pendulum subjected to a time-periodic follower force. Different values of the pendulum length are considered. Simulation results are exposed to illustrate the effect of OFCHA in comparison with FCHA and CFC.